2020
DOI: 10.1590/1806-93042020000100015
|View full text |Cite
|
Sign up to set email alerts
|

Longer duration of exclusive breastfeeding reduces maternal weight retention: results from the CLaB study

Abstract: Objectives: to evaluate the relation between breastfeeding and postpartum weight reten-tion. Methods: this prospective cohort study involved 641 newborns and their mothers, followed up to twelve months postpartum. Data were collected from June 2015 to February 2017. In the first interview, we investigated data regarding socioeconomic and demographic characteristics, obstetric history, weight, and gestational age of the infant at birth. Maternal weight and breastfeeding status were obtained at 3, 6, 9 and 12 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
1
0
2
Order By: Relevance
“…36 This observation aligns with prior research indicating that maternal health literacy alone does not significantly predict EBF outcomes. 37 The study found no significant relationship between Islamic belief and EBF among Thai Muslim mothers. Despite nearly half having a strong Islamic belief, cultural and religious practices, such as the requirement for modesty, may complicate breastfeeding, especially in public.…”
Section: Pacific Rim Int J Nurs Res • April-june 2024mentioning
confidence: 74%
“…36 This observation aligns with prior research indicating that maternal health literacy alone does not significantly predict EBF outcomes. 37 The study found no significant relationship between Islamic belief and EBF among Thai Muslim mothers. Despite nearly half having a strong Islamic belief, cultural and religious practices, such as the requirement for modesty, may complicate breastfeeding, especially in public.…”
Section: Pacific Rim Int J Nurs Res • April-june 2024mentioning
confidence: 74%
“…Kunci keberhasilan latihan ROM adalah konsistensi. Melakukan latihan secara teratur membantu mempertahankan dan meningkatkan fleksibilitas serta rentang gerak tubuh (Alves et al, 2020;Lim & Hyun, 2021;Wang et al, 2021;Yang et al, 2020). Jika selama latihan muncul tanda-tanda seperti nyeri yang berkepanjangan, bengkak, atau ketidaknyamanan yang tidak wajar, segera hentikan latihan dan dapatkan saran medis.…”
Section: Pembahasanunclassified
“…Estudo de coorte prospectiva, com foco na atenção à saúde de lactentes nascidos prematuros tardios, ele se configura como um subprojeto da pesquisa de base populacional denominada 'Saúde da criança no primeiro ano de vida: estudo de coorte prospectiva no interior paulista' -coorte de lactentes de Botucatu (CLaB). 10 O estudo da CLaB 10 escolheu este município de médio porte do interior do estado de São Paulo, Brasil, cujos serviços de atenção primária à saúde infantil, em funcionamento durante o acompanhamento da coorte, totalizavam 21 unidades de saúde de caráter público: dois centros de Saúde Escola, seis unidades básicas de saúde e 12 unidades da Estratégia Saúde da Família, além de um serviço de saúde municipal de atenção e triagem neonatal. O município também conta com 37 clínicas/consultórios pediátricos privados.…”
Section: Métodosunclassified